Building resilience: Over 550 Ethiopian wheat producers enabled with bundled sustainable agroecological innovations - Mockshell, Jonathan; Tibebe, Degefie; Ngige, Chris Mwangi; Balcha, Yodit; Ibrahim, Mohamed; Ritter, Thea; Ogutu, Sylvester (2025)
Ethiopian wheat producers lack access to affordable fertilizer and seeds. A TRANSITIONS Private Sector Incentives and Investments (PSii) sustainability project provided bundled agroecological solutions, including faba bean and wheat crop rotation to enhance nitrogen fixation and biodiversity. In addition to training wheat producers in Doyogena, the project provided subsidized inputs and enhanced partnerships between producer organizations, district agricultural offices, seed breeders, and other stakeholders in the wheat value chain. Immediate outcomes include increased awareness, the adoption of farm-level agroecological solutions, and increased empowerment.